MIMO-OFDM WLAN Architectures, Area Coverage, and Link Adaptation for Urban Hotspots - Bian, Y.Q.; Nix, A.R.; Tameh, E.K.; McGeehan, J.P. (IEEE transactions on vehicular technology, 2008)
This paper considers the suitability of a range of multi-input-multi-output (MIMO) orthogonal frequency-division multiplexing architectures for use in urban hotspots. A ray-tracing propagation model is used to produce realistic MIMO channel data. This information is used to determine the expected throughput and area coverage for various physical (PHY) layer schemes. Site-specific throughput predictions are generated in a city-center environment. Link adaptation (LA) is shown to play a key role in the choice of space-time algorithm, the use of adaptive modulation and coding, and the number of antennas employed at both ends of the radio link. No single PHY layer scheme is suitable to cover the entire coverage area. Results demonstrate the need for MIMO LA under a wide range of channel conditions. For the area under test, 2% of covered locations selected a spatial multiplexing (SM) scheme, 50% selected a space-time block coding (STBC) scheme, and 48% selected a hybrid SM/STBC scheme. With suitable power control and LA, for the scenario under consideration, high peak capacities and good geographic coverage were achieved.